KORELASI ANTARA SELF-ESTEEM DAN SELF-IMAGE DENGAN PERILAKU KONSUMTIF PADA SISWI SMA - Muhammad Aldi; jarkawi; Sri Ayatina Hayati (Prodi Bimbingan dan Konseling Islam, 2025)
The consumptive behavior experienced by female high school students leads them to purchase unnecessary, less necessary, or inappropriate items. This results in money wastage, the formation of reference groups, and the creation of false needs. This study aims to determine whether there is a relationship between consumptive behavior and the independent variables of self-esteem and self-image. The subjects of this study were 99 tenth-grade female students at SMA Negeri 12 Banjarmasin. The researchers used Pearson product-moment hypothesis testing and multiple correlation analysis with SPSS 21. The results of the Pearson product-moment significance test and the two-way significance multiple correlation analysis were 0.000, and the F change significance was 0.000, meaning sig. < 0.05, indicating a significant relationship between the variables. The Pearson correlation for variable X1 with Y and variable X2 with Y was 0.576 & 0.569, both indicating a fairly strong correlation. The multiple correlation between X1 & X2 with Y was 0.596, indicating a fairly strong correlation among the three variables. In conclusion, the higher/positive the self-esteem and self-image, the greater the consumptive behavior, or vice versa Keywords: Self-Esteem, Self-Image, Consumptive Behavior